Inversión pública y calidad de vida de los pobladores de la Municipalidad Distrital de Jenaro Herrera 2024 - Perea Sandi, Victor Mitchel (2025)
The objective of this research work was to determine how public investment influences the quality of life of the residents of the District Municipality of Jenaro Herrera 2024. The study is of a basic type, with a quantitative approach, correlational cross-sectional type, non-experimental design. The sample consisted of 100 residents. In this study, the survey and the questionnaire were used as instruments. In the results it could be observed that, out of a total of 350 respondents in Public Investment and Quality of Life of the Residents of the District Municipality of Jenaro Herrera 2024, 5.6% responded that they totally disagree with public investment in the District Municipality of Jenaro Herrera 2024, therefore, 6.6% commented that they disagree, in addition 20.3% stated that they neither agree nor disagree, on the other hand, 22.6% expressed that they agree, meanwhile, 44.9% stated that they totally agree with public investment in the District Municipality of Jenaro Herrera 2024. Concluding that public investment positively influences the quality of life of the residents of the District Municipality of Jenaro Herrera 2024, highlights the importance of efficient management and oriented towards social welfare. This implies that public resources are being strategically channeled towards sectors that directly impact the living conditions of citizens.